Characteristics of Historiography and Source Base of Research of the Problem of Succession in Labour Education of Children of Preschool and Junior School Age (End of the XIX Century – 1930-s) - Yevhen Antypin (Pedagogical Discourse, 2013)
The article shows characteristics of historiography and source base for the research of continuity in labor education of preschool and primary school children in the national educational thought (end of XIX – 30-th years of XX century). The common ideas of classification of historiography and the source base is shown. Submitted the characteristics of chronological limits of historical and pedagogical problem. Underlined the groups of sources: literal (reference, scientific, journalistic), archival (regulations, original documentation, secondary documentation, personal documents, memoirs, statistical materials). Pointed out the key aspects of researching of represented problem.